A Case for Offering HPV Self-Sampling to Well-Screened Women. Comment on Lesack et al. Willingness to Self-Collect a Sample for HPV-Based Cervical Cancer Screening in a Well-Screened Cohort: HPV FOCAL Survey Results. Curr. Oncol. 2022, 29, 3860–3869 - Roni Kraut; Donna Manca; Aisha Lofters; Oksana Babenko (Current Oncology, 2022)
Lesack et al. recently published a cross-sectional study that focused on human papillomavirus (HPV) self-sampling in the screened population, a population not conventionally thought of for HPV self-sampling. They found 52% of well-screened, highly educated women who participated in the Human Papillomavirus For Cervical Cancer (HPV FOCAL) screening trial in British Columbia, Canada, would be willing to self-collect an HPV sample. We published a similar study in 2021 on well-screened, highly educated women affiliated with a family medicine clinic in Edmonton, Alberta, Canada, and found that 60% of these women preferred to have the option of HPV self-sampling. Our findings reinforce Lesack et al.’s results and together provide evidence for offering HPV self-sampling as an option for the well-screened population.